Comparison between the effects of exergame intervention and traditional physical training on improving balance and fall prevention in healthy older adults: a systematic review and meta-analysis - Yan Chen (BMC, 2021)
Abstract Objective Physical training (PT, e.g., Tai Chi and strength training) has been demonstrated to improve balance control and prevent falls. Recently, exergame intervention (EI) has emerged to prevent falls by enhancing both physical and cognitive functions in older adults. Therefore, we aim to quantitatively assess and compare the effects of PT and EI on the performance of balance control and fall prevention in healthy older adults via meta-analysis. Methods A search strategy based on the PICOS principle was used to find the publication in the databases of PubMed, EMBASE, Web of Science, Cochrane Library, and MEDLINE. The quality and risk of bias in the studies were independently assessed by two researchers. Results Twenty studies consisting of 845 participants were included. Results suggested that as compared to PT, EI induced greater improvement in postural control (sway path length, SMD = − 0.66, 95% CI − 0.91 to − 0.41, P < 0.001, I 2 = 0%; sway speed, SMD = − 0.49, 95% CI − 0.71 to − 0.27, P < 0.001, I 2 = 42%) and dynamic balance (SMD = − 0.19, 95% CI − 0.35 to − 0.03, P = 0.02, I 2 = 0%) in healthy older adults. The EI with 90–119 min/week for more than 8-week significantly reduced falls. Subgroup analyses revealed that exergames, which were designed by the two principles of repeatedly performing diversified tasks and gradually increase the difficulty of the task, induced significant effects in improving balance control and falls prevention respectively (P = 0.03, P = 0.009). In addition, intervention that combines EI and PT induced significant improvement in postural control (P = 0.003). Conclusion The exergame intervention, especially the combination of EI and PT, is a promising strategy to improve balance control and reduce falls in healthy older adults. Future studies with rigorous design, larger sample size, and follow-up assessments are needed to further assess the effectiveness of diverse exergame interventions in fall prevention and to quantify the “dose-effect” relationship, as well as the carry-over effect of such intervention, which will ultimately help optimize the rehabilitative strategies to improve balance control and prevent falls.